Structural modeling of phosphatidylinositol 3-kinase-γ with novel derivatives of stilbenoids - Sagar Rathee; Madhan Vishal Rajan; Simran Sharma; Gururao Hariprasad (Biochemistry and Biophysics Reports)
Phosphatidylinositol 3-kinases (PI3K) form a family of lipid kinases that catalyze the phosphorylation of 3-hydroxyl group of the inositol ring of phosphatidylinositol and its derivatives. It is implicated in inflammatory disorders and cancer thus making it an attractive drug target. Crystal structure of human PI3Kγ was taken and structure was completed using MODELLER and validated using PROCHECK. Stilbenoid molecules, piceatannol and resveratrol, were docked to kinase domain of PI3Kγ using AutoDock Vina and docked complexes were subjected to molecular dynamic simulations using Desmond suite of programmes. Based on the structural analysis of these complexes, modified derivatives of the native molecules were designed, docked and molecular dynamic simulations were performed. Kinase domain has a bi-lobar structure with ATP binding site lying in the cleft connecting the two lobes that are primarily composed of 12 α-helices and 8 β-strands. Piceatannol and resveratrol bind at the ATP binding site, with one its rings in a position primarily occupied by adenine of ATP making a hydrogen bond with backbone of Val882. Molecules also make interactions with Lys833 and several isoleucine residues. Interactions with Ser806 appear to be crucial for the loop conformation and compactness. Derivative molecules of stilbenoids also occupy the ATP binding cleft and the chemical modifications result in hydrogen bonded interactions to Glu880, and ionic interactions to Lys833 and Lys808 thereby enhancing their potencies in comparison to native molecules. Biophysical parameters and quality of interactions of stilbenoid derivatives augurs well for development of potent and specific inhibitory molecules against PI3Kγ enzyme.